1997
DOI: 10.1103/physrevb.55.16159
|View full text |Cite
|
Sign up to set email alerts
|

Domain freezing in potassium dihydrogen phosphate, triglycine sulfate, and CuAlZnNi

Abstract: The temperature dependence of the dielectric constant and dissipation in potassium dihydrogen phosphate ͑KDP͒, its deuterated compound ͑DKDP͒, triglycine sulfate ͑TGS͒, and TGS doped with ␣-alanine ͑LATGS͒ has been studied at various frequencies. It is found that the relaxation time of domain freezing in KDP and DKDP in the kHz range can be described by the Vogel-Fulcher relation. Evidence of domain freezing in TGS is presented through an analysis of relaxation time related to domain walls and a comparison bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
66
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 33 publications
10
66
0
1
Order By: Relevance
“…Huang et al (1997) found evidence of superelasticity in the CuAlZnNi alloy. Kityk et al (2000) systematically compared the elastic behaviour of SrTiO 3 as measured at low frequencies (10±45 Hz) with the results of ultrasonic and Brillouin scattering experiments, which operate in the kHz± GHz range.…”
Section: Domain Walls and Anelasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al (1997) found evidence of superelasticity in the CuAlZnNi alloy. Kityk et al (2000) systematically compared the elastic behaviour of SrTiO 3 as measured at low frequencies (10±45 Hz) with the results of ultrasonic and Brillouin scattering experiments, which operate in the kHz± GHz range.…”
Section: Domain Walls and Anelasticitymentioning
confidence: 99%
“…Examples include the softening of c 66 in KD 2 AsO 4 (Fally et al, 1995), and internal friction measurements in KDP, DKDP and TGS (Huang et al, 1997). Bourim et al (2002) have observed anelastic behaviour in PZT, associated with the ferroelectric domains.…”
Section: Domain Walls and Anelasticitymentioning
confidence: 99%
“…In particular, this is an effect of a sharp decrease of the dielectric constant with lowering temperatures below a certain value. It must be mentioned that a similar behavior is typical of many ferroelectrics: KDP [1], PbTiO 3 [2], SBN [2]. In most cases it was attributed to a freezing of domain walls dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases it was attributed to a freezing of domain walls dynamics. This phenomenon was very intensively studied in the crystals of KDP family (see references in the paper [1]). An analysis of the relaxation dispersion observed in polydomain TGS crystals far below T c in the ferroelectric phase [1] reveals that the domain freezing effect occurs in this material as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation